Efektifitas Model Pembelajaran Online Co-Construction Pada Matakuliah Manajemen Pendidikan Anak Usia Dini - Trihantoyo, Syunu; Nuri Herachwati; Rudi Purwono; Supriyanto; Mohamad Syahidul Haq; Windasari; Wahyu Purwaningayu Galih (Universitas Pendidikan Ganesha, 2023)
The challenge of online learning in higher education is that there is often a lack of focus on students taking part in lectures, which causes a loss of learning. This study aims to analyze the feasibility and effectiveness of the co-construction online learning model in early childhood education management courses. The research method uses a research and development approach with the ADDIE model. Data collection was carried out by interviews, questionnaires, and observations on 88 students taking early childhood education management courses. Product feasibility testing was carried out from questionnaire data analysis on 10 statement items using a four-rating scale, while observations and interviews were used to analyze the effectiveness of implementing the co-construction online learning model. Data analysis used qualitative descriptive and quantitative techniques to analyze the feasibility and effectiveness of implementing the co-construction online learning model. The results of the study in the electronic feasibility test for teaching materials achieved a score of 71.4%, which means it is feasible and does not need revision. While the effectiveness test was carried out twice with different timeframes, in the first data collection there were 73% of active students, then it increased in the second data collection with 88% of active students. This increase is to Skinner's theory of operant conditioning learning, where individual behavior is influenced by the repetition of actions received.